A NEXT GENERATION? YOUNG DUTCH REFORMED CHURCH MINISTERS AND THEIR VISION FOR THE CHURCH IN SOUTH AFRICA - G.J. Van Wyngaard (Acta Theologica)
For the foreseeable future, the Dutch Reformed Church will be remembered for its role in the theological justification of apartheid and spiritual support for the leaders driving this political process. Questions on the faith, theology, and spirituality that made this theological and spiritual support possible have been analysed in detail over decades. This church is, however, poised to see a generation of ministers, who were trained after the Dutch Reformed Church’s position on apartheid changed, and after the end of apartheid in South Africa, taking over the leadership of this denomination. This article analyses responses to a 2019 survey among Dutch Reformed Church ministers and licensed proponents aged younger than forty years. Utilising a 7-point praxis matrix, it highlights the way in which these respondents describe the current ecclesial praxis and discern the future calling of the church. It focuses particularly on how they relate to the church’s past, and its historically White identity.